2003
DOI: 10.1029/2001jc001243
|View full text |Cite
|
Sign up to set email alerts
|

Winter mesoscale variations of carbonate system parameters and estimates of CO2 fluxes in the Gulf of Cadiz, northeast Atlantic Ocean (February 1998)

Abstract: [1] Further observations with small spatial and temporal resolutions conducted during different seasons are required in order fully to understand the role that shelves play in the global carbon cycle. The components of the carbonate system (total alkalinity, pH in the total scale, total dissolved inorganic carbon, and CO 2 fugacity), and dissolved oxygen, nutrients, and phytopigments were studied along the mesoscale section over the continental shelf and slope in the Gulf of Cadiz in February 1998. All the che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
5
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 48 publications
4
5
0
Order By: Relevance
“…The A T concentrations measured and associated to the occurrence of NASW have been observed previously in the Strait of Gibraltar as well as in the nearby Gulf of Cadiz Aït-Ameur and Goyet, 2006). Also, available C T values for the North East Atlantic Central Water (Ríos et al, 1995;González-Dávila et al, 2003) are consistent with those reported here in the inflow of the Atlantic water passing through the Strait.…”
Section: The Carbon System Parameters In the Strait Of Gibraltarsupporting
confidence: 79%
See 1 more Smart Citation
“…The A T concentrations measured and associated to the occurrence of NASW have been observed previously in the Strait of Gibraltar as well as in the nearby Gulf of Cadiz Aït-Ameur and Goyet, 2006). Also, available C T values for the North East Atlantic Central Water (Ríos et al, 1995;González-Dávila et al, 2003) are consistent with those reported here in the inflow of the Atlantic water passing through the Strait.…”
Section: The Carbon System Parameters In the Strait Of Gibraltarsupporting
confidence: 79%
“…3f, Table 2), the discrepancies existing between the carbon exchanges in the literature can be attributable to the values of the water transport associated to each water layer. High values of carbon exchange result when water transports given by Béthoux (1979) are used for fluxes computation, as already underlined by other authors (Gómez, 2003;Aït-Ameur and Goyet, 2006). This circumstance may be due to the fact that the early work by Béthoux (1979) did not consider properly the interface definition for calculations.…”
Section: Discussionmentioning
confidence: 76%
“…The Gulf of Cádiz acts as a source of CO2 to the atmosphere during the months of summer (ST2, ST6) and autumn (ST3, ST7), and as a sink in spring (ST1, ST5) and winter (ST4, ST8). Previous studies conducted in the Gulf of Cádiz are consistent with the behaviour found in this study (González-Dávila et al, 2003;Aït-Ameur and Goyet, 2006;Ribas-Ribas et al, 2011).…”
Section: Ocean-atmosphere Co2 Exchange 420supporting
confidence: 93%
“…The Gulf of Cádiz, during the period of this sampling, acted as a sink of CO2, with a mean rate of -0.18 ± 1.32 mmol m -2 d -1 , that would give rise to an annual flux of -0.07 mol C m -2 yr -1 . The findings of previous studies carried out in the Gulf of Cádiz coincide with the behaviour observed in this study (Santana-Casiano et al, 2002;González-Dávila et al, 2003;Huertas et al, 2006;de la Paz et al, 2009;Ribas-Ribas et al, 2011), with the exception of the study by Aït-Ameur and Goyet (2006) in which it was estimated that the Gulf of Cádiz acts as a source of CO2 to the atmosphere, although that study only corresponds to the summer season.…”
supporting
confidence: 88%
See 1 more Smart Citation